2007
DOI: 10.2337/db07-0093
|View full text |Cite
|
Sign up to set email alerts
|

Excess Lipid Availability Increases Mitochondrial Fatty Acid Oxidative Capacity in Muscle

Abstract: A reduced capacity for mitochondrial fatty acid oxidation in skeletal muscle has been proposed as a major factor leading to the accumulation of intramuscular lipids and their subsequent deleterious effects on insulin action. Here, we examine markers of mitochondrial fatty acid oxidative capacity in rodent models of insulin resistance associated with an oversupply of lipids. C57BL/6J mice were fed a high-fat diet for either 5 or 20 weeks. Several markers of muscle mitochondrial fatty acid oxidative capacity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
174
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(211 citation statements)
references
References 51 publications
27
174
0
Order By: Relevance
“…We first examined the phosphorylation state of CaMKII in a chronic model of obesity, namely obese Zucker rats, which are known to have higher levels of skeletal muscle mitochondrial content (2,20). We have confirmed these findings because mtDNA was increased (P , 0.05) approximately twofold in obese animals (Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…We first examined the phosphorylation state of CaMKII in a chronic model of obesity, namely obese Zucker rats, which are known to have higher levels of skeletal muscle mitochondrial content (2,20). We have confirmed these findings because mtDNA was increased (P , 0.05) approximately twofold in obese animals (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…However, high-fat feeding has been shown to induce insulin resistance while increasing mitochondrial content (2,3), divorcing this proposed causal relationship. Nevertheless, a reduction in mitochondrial content could exacerbate the phenotype of insulin resistance (4), whereas the increase in mitochondrial content observed at the initiation of a high-fat diet is likely beneficial because genetic approaches that modestly increase mitochondrial content improve insulin signaling in insulin resistant animals (5).…”
mentioning
confidence: 99%
“…From the viewpoint of energy consumption, the SKL‐14959‐treated group did not significantly enhance β‐HAD activity in the liver and the muscle (Figure 2D–2F) nor significantly up‐regulate the relative gene expression of PPAR‐alpha ( ppara ) in the liver and the adipose tissue, UCP‐2 ( ucp2 ) and hormone sensitive lipase ( Lipe ) in the adipose tissue compared with the HFD control group (Figure 4A and 4B). It might be because GLP‐1 made up for the effect 31; alternatively, raised β‐HAD activity in the HFD control group compared with the LFD group was already reached maximal effectiveness, so that further combustible effects of SKL‐14959 were not observed 32. These results suggested that SKL‐14959 might not have direct action or have only a subtle effect of lipolysis.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, control mice fed HFD had lower VO 2 than control mice fed STD. These data suggest that in Ames dwarf mice oxygen consumption is not affected by HFD feeding, possibly reflecting that an increase in respiration is linked to an increase in fatty acid oxidation (Garcia‐Roves et al ., 2007; Turner et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%